Does the Loan Loss Provision Affect the Banking Profitability in Case of Pakistan? - Mustafa, Ahmed Raza ul; Ansari, Riaz Hussain; Younis, Muhammad Umair (Asian Economic and Financial Review, 2012)
This paper examines the impact of loan loss provisions of the banks on the performance of the banks operating in Pakistan. Moreover the other factors that affect the banking profitability have been discussed in this study. Our results show that the loan loss provision of the banks is of paramount importance in affecting its profitability. A well-managed bank is perceived to be of lower loan loss provision and such an advantage will be translated into higher profitability. In addition, banks advances and deposits which represent the vital role for the determination of banking profitability. Finally, with regard to non financial variable, political instability in the previous period has more significant effect on the present banks profitability rather than the political instability at present period.